(untitled) (Arquivo Maaravi: Revista Digital de Estudos Judaicos da UFMG, 2021)
In the first half of the 20th century, Brazil received immigrants from the most varied countries, which undoubtedly marked the development of its society and culture. At first, the immigrant, and their cultural baggage, still preserved their customs, trying, at the same time, to adapt to the new society. Among the immigrants who arrived in Brazil, there are Jews from Europe and the Middle East. Immigration is often synonymous with displacement, leaving a place and not belonging anywhere. This feeling is expressed in A guerra no Bom Fim, 1972, by Moacyr Scliar, and A hora da estrela, published in 1977, by Clarice Lispector. This communication will study this immigration condition in the two novels, considering that the immigration process includes stages of adaptation, integration, and assimilation.